2007
DOI: 10.1016/j.imavis.2006.05.012
|View full text |Cite
|
Sign up to set email alerts
|

A review of recent range image registration methods with accuracy evaluation

Abstract: The three-dimensional reconstruction of real objects is an important topic in computer vision. Most of the acquisition systems are limited to reconstruct a partial view of the object obtaining in blind areas and occlusions, while in most applications a full reconstruction is required. Many authors have proposed techniques to fuse 3D surfaces by determining the motion between the different views. The first problem is related to obtaining a rough registration when such motion is not available. The second one is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
314
0
8

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 553 publications
(331 citation statements)
references
References 37 publications
2
314
0
8
Order By: Relevance
“…Standard alignment techniques use the Iterative Closest Point (ICP) algorithm [22] which solves data association at a point-to-point level 1 . However, as noted in the literature [23] and as shown in the proposed experiments, this method fails when nearest points do not correspond to correct association (illustrated in Fig. 3).…”
Section: Introductionsupporting
confidence: 55%
See 1 more Smart Citation
“…Standard alignment techniques use the Iterative Closest Point (ICP) algorithm [22] which solves data association at a point-to-point level 1 . However, as noted in the literature [23] and as shown in the proposed experiments, this method fails when nearest points do not correspond to correct association (illustrated in Fig. 3).…”
Section: Introductionsupporting
confidence: 55%
“…A recent survey [23] shows that 3D alignment techniques have converged around one main pipeline which involves two broad steps: coarse alignment followed by fine alignment. Coarse alignment uses for instance Principal Component Analysis [15] or feature based matching with features such as the Spin Image [14] to compute an initial coarse registration.…”
Section: Introductionmentioning
confidence: 99%
“…Salvi et al [13] found the DARCES method [17] to be the most robust method for range image registration, and DARCES is also the closest published method to the one we are using in this paper. The most important difference between DARCES and the presented method is that DARCES is based on the presence of three points, while our method only requires two points.…”
Section: Introductionmentioning
confidence: 62%
“…Existing methods in this field can be grouped into coarse and fine registration methods [13]. The goal of coarse registration methods is to compute an initial estimate of the rigid motion of the object, which eventually can be refined by more precise methods later.…”
Section: Introductionmentioning
confidence: 99%
“…Other approaches used to reject invalid matches based on some compatibility test Turk and Levoy (1994); Masuda et al (1996); Dorai et al (1998) also depend on the 3D sensor used. In Salvi et al (2007) a deeper study comparing different solutions for ICP in terms of speed and accuracy is performed. Nowadays, more ICP variations are still appearing Du et al (2007a,b); Nuchter et al (2007);Censi (2008); Armesto et al (2010).…”
mentioning
confidence: 99%